2017
DOI: 10.1371/journal.pone.0188573
|View full text |Cite
|
Sign up to set email alerts
|

Pore-forming activity of new conjugate antibiotics based on amphotericin B

Abstract: A series of amides of the antifungal antibiotic amphotericin B (AmB) and its conjugates with benzoxaboroles was tested to determine whether they form pores in lipid bilayers and to compare their channel characteristics. The tested derivatives produced pores of larger amplitude and shorter lifetime than those of the parent antibiotic. The pore conductance was related to changes in the partial charge of the hydrogens of the hydroxyl groups in the lactone ring that determined the anion coordination in the channel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 44 publications
3
19
0
1
Order By: Relevance
“…Therefore, water-stable and well-dispersed aqueous solutions of AmB with low toxicity and reduced manufacturing costs remain a priority. New derivatives of AmB for improved water solubility, antifungal efficacy, and reduced cytotoxicity were synthesized 52,7274. In general, the single amine and single carboxylic group of AmB were preferred for chemical modification75,76 where modification of the AmB amine group was found to be more effective in reducing the cytotoxicity77 without compromising efficacy52 against fungus.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, water-stable and well-dispersed aqueous solutions of AmB with low toxicity and reduced manufacturing costs remain a priority. New derivatives of AmB for improved water solubility, antifungal efficacy, and reduced cytotoxicity were synthesized 52,7274. In general, the single amine and single carboxylic group of AmB were preferred for chemical modification75,76 where modification of the AmB amine group was found to be more effective in reducing the cytotoxicity77 without compromising efficacy52 against fungus.…”
Section: Discussionmentioning
confidence: 99%
“…12 , 13 , 17 This mechanism continues to appear in modern textbooks and publications, including by groups aiming to improve the pharmaceutical properties of AmB or other GPMs. 18 22 However, recent studies have decoupled ion channel formation from the fungicidal activity of AmB and shown that only glycosylation-dependent ergosterol sequestration is essential. 9 , 15 , 23 Specifically, a synthetic derivative of AmB lacking a C35 hydroxyl group did not form ion channels but retained ergosterol binding and fungicidal activity.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, benzoxaboroles are known to enhance the transport of macromolecules into the cell as a result of the interaction with 1,2- and 1,3-diol polysaccharides located on the cell surface. These properties, as well as the ability of some heterocyclic boronic acids and benzoxaborole derivatives to exhibit activity against Gram-negative bacteria with multi-drug resistance, were considered when developing chimeric antibiotics based on glycopeptides or polyene macrocyclic antibiotics containing benzoxaboroles in their structure [ 6 , 12 ] and benzoxaborole derivatives of azithromycin [ 8 ].…”
Section: Introductionmentioning
confidence: 99%